Mutant BCL11B in a Patient With a Neurodevelopmental Disorder and T-Cell Abnormalities - Yang, Sai; Kang, Qingyun; Hou, Yanqi; Wang, Lili; Li, Liping; Liu, Shulei; Liao, Hongmei; Cao, Zhenhua; Yang, Liming; Xiao, Zhenghui (Frontiers in Pediatrics, 2020)
Background BCL11B encodes B cell lymphoma/leukemia 11B, a transcription factor that participates in the differentiation and migration of neurons and lymphocyte cells. De novo mutations of BCL11B have been associated with neurodevelopmental disorder and immunodeficiency. These mutations were identified in patients with Immunodeficiency 49 (IMD49) or Intellectual developmental disorder with speech delay, dysmorphic facies, and T-cell abnormalities (IDDSFTA). However, the pathogenesis of these two types of neurodevelopmental disorder and T-cell deficiency is still mysterious. The strategy to distinguish these two diseases in detail is also unclear. Methods We identified a patient with unique clinical features and applied multiple examinations for evaluation. Whole-exome sequencing (WES) and Sanger sequencing were also used to determine the disease-causing mutation. Results We report a 17-month-old girl of intellectual disability with motor and speech delay. She presented dysmorphic facial features and week functional movement. MRI displayed the abnormal myelination of the white matter. Immunological analysis indicated normal levels of RTEs and γδT cells but a deficiency of naïve T-cells. Sequencing analysis identified that a de novo heterozygous frameshift c.1192_1196delAGCCC presented in the BCL11B gene. Conclusions We reported the first IDDSFTA patient of East Asian origin. The unreported neurological display, immunophenotype, and a novel disease-causing mutation of the patient extended the spectrum of clinical features and genotype of IDDSFTA. Keywords: BCL11B, neurodevelopmental disease, immunodeficiency, developmental disorder, immune system abnormalities